Community-Centered Plastic Waste Management: Leveraging Household Participation via Waste Bank in Padang, Indonesia - Alfitri Alfitri; Afrizal Afrizal; Slamet Raharjo; Lucky Zamzami; Sudarmanto Budi Nugroho; Van Huynh Thanh Pham (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
Plastic waste in Indonesia threatens environmental sustainability and health. This study explores waste bank as a social innovation based on the 3R principle, as a means of education, behavior change in waste management, and the implementation of the circular economy. Aims: This study aims to identify and describe the practices and reasons of household participation in waste bank, also the efforts of administrators to increase it. Methodology and results: Using Giddens' structuration theory and a mixed-methods approach, this study indicates promising results regarding the participation process in plastic waste management at the community level. This article examines a case of a waste bank, which is developing well in the city of Padang, Indonesia. The results revealed that most customers of the waste bank deposit plastic waste biweekly, where generally household members are involved in sorting waste at home. Conclusion, significance and impact study: The cause of the high level of household participation is a combination of environmental awareness and economic incentives. Household participation is relatively high and gives hope for sustainable plastic waste management. The efforts of waste bank administrators provide additional services leveraging household participation in waste bank. Awareness to protect the environment is the main driver of household participation. The innovation of waste pick-up services using motorcycle rickshaws implemented by the management of the Waste Bank. The use of waste bank in managing plastic waste will have an impact on achieving SDG 11.6.